2019
DOI: 10.1186/s12882-019-1216-2
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of different serum phosphate ranges in subjects on hemodialysis

Abstract: BackgroundHyperphosphataemia in dialysis subjects is associated with increased mortality. However cause and effect has not been proven, and the ideal phosphate target range is unknown despite KDOQI’s call for studies over 12 years ago. The design and conduct of a randomized controlled trial is challenging because maintaining two groups within differing target ranges of serum phosphate has not been achieved over a long follow-up of 1 year, in a trial setting, before. The SPIRiT study examines the subject accept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Among the patients with elevated Pi levels, 29.4% had diabetes mellitus. In comparison, of those with low Pi levels, 20.8% had diabetes mellitus (42), which was confirmed by another study (25). However, we found that the elderly patients (Group B) who had more diabetics had lower Pi levels than the younger ones (Group A).…”
Section: Discussionsupporting
confidence: 82%
“…Among the patients with elevated Pi levels, 29.4% had diabetes mellitus. In comparison, of those with low Pi levels, 20.8% had diabetes mellitus (42), which was confirmed by another study (25). However, we found that the elderly patients (Group B) who had more diabetics had lower Pi levels than the younger ones (Group A).…”
Section: Discussionsupporting
confidence: 82%
“…Nearly half of patients in the intensive group achieved their phosphate targets with calcium carbonate alone and most participants in the liberal phosphate target group achieved their target without the use of binders at all. The SPIRIT trial, which randomized 104 HD patients to a lower (2.5–4.3 mg/dL) or higher phorphorus target (5.6–7.4 mg/dL) also achieved a clinically significant sustained separation over 12 months [ 24 ]. It would have been interesting to see what role the AUC approach could have to better define the two target strategies used in this trial.…”
Section: Discussionmentioning
confidence: 99%
“…Serum phosphate levels have been identified as strong predictors on clinical outcomes, including hospital mortality [4]. While hypophosphatemia is shown to be independently associated with increased mortality among critically ill patients, malnourished individuals, and patients with sepsis [5][6][7], hyperphosphatemia is associated with poor clinical outcomes including mortality in chronic kidney disease (CKD) [8,9], hemodialysis [10,11], acute coronary syndrome [12], and general patient population [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%